Patient satisfaction with radio-frequency identification (RFID) tag localization compared with wire localization for nonpalpable breast lesions: the RFID trial - Raphaël Pete; Céleste Pinard; Fanny Sirodot; Ioana Molnar; Margot Dressaire; Angeline Ginzac; Catherine Abrial; Xavier Durando; Marielle Tekath (BMC Cancer)
Abstract Background Most breast cancers are detected at an early stage in which case conservative surgery is indicated. An accurate preoperative localization technique is essential for conservative surgery of non-palpable breast lesions. Currently, the gold standard technique is wire localization (WL). However, this technique has well-known drawbacks. Several wire-free techniques have been developed to overcome these drawbacks; one technique is localisation by Radiofrequency Identification (RFID). The purpose of this clinical trial was to assess the superiority of RFID tags (HOLOGIC) in terms of patient satisfaction, over wire localization of non-palpable breast lesions. Methods This was a single-centre, prospective, controlled and non-interventional trial. Patients were followed from their inclusion at the time of the preoperative consultation to the postoperative consultation, one month after surgery. Data on anxiety and satisfaction was collected from patients and clinicians using questionnaires, and clinical data was collected from the medical files. The primary outcome was the patients’ satisfaction scores, assessed using a visual analogue scale. Results Eighty patients were sequentially enrolled in two groups: the wire group (n = 40) and the RFID group (n = 40). One patient from the RFID group was excluded from the analysis because of a substantial migration during deployment. On a 10-point Visual Analogue Scale, the patients’ median satisfaction score was 9.8 (IQR = 1.32) for the wire group and 10 (IQR = 0.07) for the RFID group (p < 0.001). A reduction in pain between device insertion and surgery was observed in the RFID group (p = 0.009). The median placement time was shorter in the RFID group (15 min, IQR = 6) than in the wire group (20 min, IQR = 30) (p = 0.01). Conclusion Our results show a statistically significant difference in median patient satisfaction score with the localization of non-palpable breast cancer lesions using RFID tags compared to the use of the WL. Although our results did not show clinically significant outcomes in terms of satisfaction, RFID tags are a reliable alternative to WL and simplify the organization of patients’ healthcare trajectories. Trial registration ClinicalTrials.gov ID; NCT04750889 registered on February 11, 2021. https://clinicaltrials.gov/ct2/show/NCT04750889?term=rfid&draw=2&rank=1